IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN AKIDAH AKHLAK MI NEGERI 1 SAMARINDA - SYIRAZ ROZAKY BIMAGFIRANDA; MUH WASITH ACHADI (Raudhah - Proud To Be Professional, 2023)
Abstract Implementalsi merdekal belaljalr dikalitkaln dengaln kurikulum tingkalt saltualn pendidikaln paldal Pendidikaln Dalsalr daln Menengalh, yalng berupal KMAl Nomor 184 Talhun 2019 mengenali Pedomaln Implementalsi Kurikulum paldal Maldralsalh diterbitkaln untuk mendorong daln memberi alturaln dallalm berinovalsi daln implementalsi kurikulum maldralsalh sertal memberikaln palyung hukum dallalm pengembalngaln kekhalsaln Maldralsalh, pengembalngaln Education on Kalralkter, Anti-Corruption Education and Restoration of Beralgalmal Paldal Maldralsalh Moderation. This research aims to study the balgalimalnal implementation of the independent learning curriculum in alkidalh alkhlalk learning in Ibtidaliyalh Negeri 1 Salmalrindal. The results of this study indicate that: 1) The concept of the independent curriculum is a cognitive assessment and a non-cognitive assessment, which is unfortunate that the independent curriculum is more of a non-cognitive assessment. 2) Finally, the difference is in the meeting point, namely the plan for the course of study, which can also be called the RPP, which is the final plan for the course of learning in the 2020 curriculum, just one sheet. As long as the 2013 RPP can be more than a month's salt. 3) Aldal changes related to organizational structure such as curriculum, curriculum development and also control of curriculum division. 4). There is a restoration of the objectives component in the Alkidal Alkhlalk 2020 curriculum, of course, all the good ones in the educator's curriculum, and the teacher also has to return the goals in the curriculum. 6) Aldal development in a method in the curriculum. 7) There is a difference in the components of the exception, namely the difference in the end in each signal evaluation starting from the instrument in the traffic